The Absorpotion of HRST From Technology-Based Companies of Indonesia - Maulana Akbar; Ria Hardiyati (STI Policy and Management Journal, 2021)
The technology-based changes the need for more efficient human resources in science and technology (HRST). This industry has two contradictory impacts where on the one hand it increases production efficiency with automation, but on the other hand, advanced technology causes dehumanization which contributes to not being fully absorbed of HRST. This paper aims to map the absorption of the technology-based industry in Indonesia through data on job vacancies from four technology-based companies in Indonesia over a period of one year. The result is that the data shows that HRST are not absorbed in areas outside the big cities in Indonesia. On the other hand, some of the needs for HRST are distributed to the global market, especially in Singapore and Bengaluru, India. a tendency to reach the demand of HRST in the global network, especially from regions that are the world's technological centers such as Bengaluru-India and Singapore